Global Monitoring Report, 2008 : MDGs and the Environment; Agenda for Inclusive and Sustainable Development. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2008)
Global Monitoring Report 2008, the fifth in an annual series, is essential reading for those who wish to follow the global development agenda and debate in 2008. The year marks the midpoint toward the 2015 deadline for achieving the Millennium Development Goals (MDGs). It is also an important year to work toward a consensus on how the world is going to respond to the challenge of climate change, building on the foundation laid at the Bali climate change conference in December 2007. The report spans this agenda. It provides a comprehensive assessment of progress toward the MDGs and related policies and actions. It addresses the challenge of climate change and environmental sustainability and assesses its implications for development. The report's assessment of MDGs at midpoint presents a mixed picture, one of both significant progress and formidable challenges. The first MDG, reducing extreme poverty by half, is likely to be met at the global level, thanks to a remarkable surge in global economic growth over the past decade. But, on current trends, the human development MDGs are unlikely to be met. Prospects are gravest for the goals of reducing child and maternal mortality, but shortfalls are also likely in the primary school completion. nutrition, and sanitation MDGs. The potential effects of climate change compound the challenge of achieving the development goals and sustaining progress. The report's messages are clear: urgent action is needed to help the world get back on track to achieve the MDGs; and urgent action is also needed to combat climate change that threatens the well-being of all countries, but particularly of poor countries and poor people. The goals of development and environmental sustainability are closely related, and the paths to those goals have important synergies.